Student collaborative arrangements in high school jazz band - Blankenship, Hunter (Kansas State University, 2024)
This purpose of this project is to fill the gap in student knowledge of the structure and organization of a big band jazz chart and to give them an opportunity to experience using their aural skills to create their own arrangement. Students compared and contrasted elements of the arrangements of a small group “combo” jazz ensemble to that of a large “big band” jazz ensemble. They then transcribed/harmonized a jazz blues melody, learned to improvise stylistically over the chord changes, and collaborated with their sections to compose rhythmic background figures to accompany the soloists, all without using standard notation. This process resulted in a completed big band jazz arrangement that was arranged solely by the students, which they then performed on their spring concert. This Masters’ program introduced me to new perspectives and approaches to jazz education, particularly regarding improvisation. The Research in Music Education Class opened my eyes to the current research in improvisation, especially the psychological element of building confidence in beginners. The research proposal project in this class allowed me to create warm-up material for my high school beginning jazz ensemble and learn which of those warm- ups are most effective in building confidence with my beginners. Establishing this warm-up process helped to develop the culture of improvisation of this ensemble, which encouraged me to go one step further and develop the lesson plans for this Masters Report. Similarly, during the Introduction to Graduate Studies class, I was able to discover new materials and methods for teaching improvisation in a large ensemble setting. A common challenge of teaching high school jazz band is that with the quick turnaround time that is expected of the ensemble in rehearsing for adjudication festivals, school concerts, and other community events, there is seldomly enough time to devote to the seemingly daunting task of improvisation. Additionally, the individual attention necessary for proper improvisation instruction is not exactly practical in an ensemble of 20+ students. Books such as David Berger’s (2018) High School Jazz: A Director’s Guide to a Better Band and David Baker’s (1988) Jazz Pedagogy: A Comprehensive Method of Jazz Education for Teachers and Students have been invaluable resources for getting ideas to incorporate bite-sized elements of improvisation instruction into the large jazz ensemble setting without sacrificing significant rehearsal time. These resources and experiences throughout my time in the Masters’ program have given me the knowledge and tools to craft a unique experience for my high school jazz band that is authentic to the jazz idiom.
Keywords: Jazz; Jazz band; High school band; Improvisation; Composition; Arrangements